ENHANCING GEN Z EMPLOYEES COMMITMENT THROUGH FLEXIBLE WORK ARRANGEMENTS, WORK-LIFE BALANCE, AND JOB SATISFACTION - Nainggolan, Jonathan Christian Matthew; Purba, Sylvia Diana (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
This research was conducted with the aim of determining the effect of flexible working arrangements on organizational commitment with work life balance and job satisfaction as mediating variables in generation Z employees who work in Jakarta and its surroundings. In this research, the population used as the research object is generation Z employees or those with birth years from 1998 to 2009 who work in Jakarta and its surroundings. Apart from that, the purposive sampling method was used as a sample determination technique. The questionnaire distributed was in the form of a Google Form with the criteria for respondents being permanent employees who can or have worked with flexible working arrangements and have currently worked at the company for at least 1 year. 176 respondents were obtained and data processing was carried out using SMART PLS 4.0 software. The results obtained in this research are that Flexible Working Arrangement has a significant effect on Organizational Commitment, Work Life Balance, and Job Satisfaction. Job Satisfaction has a significant effect on Organizational Commitment and Job Satisfaction mediates the effect of Flexible Working Arrangements on Organizational Commitment. Meanwhile, Work Life Balance does not have a significant influence on Organizational Commitment and Work Life Balance cannot mediate the influence of Flexible Working Arrangement on Organizational Commitment.